EFEKTIVITAS EXPRESSIVE WRITING DAN MEWARNAI MANDALA DALAM MENURUNKAN KECEMASAN NARAPIDANA PEREMPUAN DI LEMBAGA PERMASYARAKATAN PEREMPUAN KELAS III GORONTALO - Rizky Towana; Nur Fadilah Musa; Anggi Putri Maulidah; Dea Pramesty Ashari; Ayu Ethika Nurhamidin; Maulidah Nur Fadilah Kum; Dea Ananda Pakaya; Intan Sekar Andini; Alisya Sitti Adawiyah Dunggio; Abdul Hakim Ismail; Thalya Leisya Hamid; Hairunnisa U Hadjarati; Fiona Adelia Rivai (program studi psikologi, 2023)
Prisoners are individuals who temporarily lose their freedom due to having to serve a criminal sentence. In general, prisoners who are in prison will experience anxiety due to extreme judgments about prisoners and demands where they must be in an environment that is of course only in one location. Therefore, researchers tried to provide mandala coloring and expressive writing treatments to reduce prisoners' anxiety. Anxiety is defined as a response to a particular experience of an unpleasant feeling, confusion, anxiety, worry, and fear. Expressing writing therapy as a writing process that is an individual expression and reflection and is done with one's own desire or the guidance of a therapist or researcher. Coloring mandalas is exactly what the name suggests, which is the process of coloring mandalas. This research was conducted at the Lembaga Permasyarakatan Kelas III Gorontalo. This research uses quantitative methods in the form of experiments. The sample amounted to 12 subjects. The anxiety scale used is TMAS (Taylor Manifest Anxiety Scale). The analysis data used is wilcoxon. The results show that 0.035 is smaller than 0.05. That means mandala coloring and expressive writing are significant as interventions to lower inmate anxiety.